1998
DOI: 10.1177/000348949810700212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surgery on Mucosal Pathologic Changes following Experimental Sinusitis in Rabbit

Abstract: In the present investigation, the regenerative capacity of the infected maxillary sinus mucosa following surgical procedures was studied in a rabbit model. Sinusitis was induced by occluding the ostium with and without the addition of Staphylococcus aureus or Bacteroides fragilis, or by provoking a prolonged bacterial infection with both pathogens. The surgical procedures performed were 1) widening of the natural sinus ostium (middle meatal antrostomy; MMA) and 2) removal of sinus mucosa without ostial interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…They concluded that the mucosa is re-epithelialized within 2 weeks, but the regeneration of the lamina propria is incomplete, and reactive cellular processes such as bone remodeling, fibroblast proliferation, and formation of polyps are characteristic of regenerating mucosa. In another study, they investigated the wound healing of the infected maxillary sinus mucosa following surgical procedures in a rabbit model, and they concluded that persistent local histopathologic changes, such as more inflammation cells, fibrosis, and bone reaction, are abundant in the ostial region following middle meatal antrostomy, irrespective of whether there was previous infection or not [16]. Consistent with the findings of the above studies, we found that the size of neo-ostium showed a significant decrease at 4 days after injury, and regenerative mucosa had more collagen deposition in the lamina propria when compared with the normal maxillary mucosa of rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the mucosa is re-epithelialized within 2 weeks, but the regeneration of the lamina propria is incomplete, and reactive cellular processes such as bone remodeling, fibroblast proliferation, and formation of polyps are characteristic of regenerating mucosa. In another study, they investigated the wound healing of the infected maxillary sinus mucosa following surgical procedures in a rabbit model, and they concluded that persistent local histopathologic changes, such as more inflammation cells, fibrosis, and bone reaction, are abundant in the ostial region following middle meatal antrostomy, irrespective of whether there was previous infection or not [16]. Consistent with the findings of the above studies, we found that the size of neo-ostium showed a significant decrease at 4 days after injury, and regenerative mucosa had more collagen deposition in the lamina propria when compared with the normal maxillary mucosa of rabbit.…”
Section: Discussionmentioning
confidence: 99%
“… Modified radical operation (MRO) as previously described 15 . In brief, this procedure consists of complete removal of the anterior part of the sinus mucosa without interfering with the ostium, and without creating a nasoantral window (23 rabbits). Middle meatal antrostomy (MMA), which consists of widening of the ostium, both anteriorly and inferiorly, to a diameter of approximately 5 mm by removing bone and mucosa (23 rabbits). …”
Section: Methodsmentioning
confidence: 99%
“…Because clinical results of this operation have been inconsistent, 3‐7 the postoperative regenerative process in experimental animal models has been a focus of interest. In accordance with clinical experience 8,9 and experimental studies, 10‐15 it is recommended not to widen the ostium routinely, but only in cases of pathologic changes in the region. One reason for caution is the importance of ensuring an adequate blood supply to the sinuses for the healing process after surgery 12,13 .…”
Section: Introductionmentioning
confidence: 97%
“…Hilding 4 pioneered the development of a rabbit model for sinusitis, which subsequently became the dominant tool with which researchers studied mucosal blood flow, lactic acid accumulation, mucosubstance histochemistry, cellular histomorphology, local and systemic humoral immune response, polyposis, and responses to a variety of thera- peutic measures. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Although the rabbit model was helpful in simulating human disease, the relative lack of experimental reagents and an inherent inability to manipulate these animals genetically have made the transition to murine research necessary. 1 To our knowledge, no mouse model for chronic bacterial rhinosinusitis exists at this time.…”
Section: Arch Otolaryngol Head Neckmentioning
confidence: 99%